THE INTERFERENCE OF SOME SASAKNESE CONSONANTS INTO ENGLISH CONSONANTS IN 2019/2020 - Masyudi Masyudi (JUPE : Jurnal Pendidikan Mandala, 2019)
This research aimed to investigate the interference of some Sasaknese consonants into English consonants in 2019/2020 by using descriptive qualitative research design. The object of this research was the pronunciation of Sasaknese native speakers in speaking English, especially that for /ʃ/, [ɹ], /θ/, /ð/, and /ʒ/. The informants of this research were 11 native speakers of Sasaknese who were able to speak English. In order to obtain the data, some of them were recorded while having dialogue with the researcher, and some others were recorded while they were performing a speech in front of their friends. The result showed that there were 182 occurrences of the investigated sounds, in which 106 were interfered by the respondents, meaning that 76 others were pronounced accurately. 12 sounds occurred in pronouncing /ʃ/ and 8 were interfered with /s/, 77 occurred in pronouncing [ɹ] and 27 were interfered with [R], 66 occurred in pronouncing /ð/ and 49 were interfered with /d/, 6 occurred in pronouncing /ʒ/ and 3 were interfered with /ʃ/, 3 others were interfered with /z/, and 21 occurred in pronouncing /θ/ with all of these sounds interfered into /t/. The interference occurred due to the absence of these sounds in standard Sasaknese consonant system and their difficulty to pronounce by Sasaknese native speakers. In addition, another cause was also the lack of respondents’ knowledge about the investigated sounds. Meanwhile, some consonants pronounced correctly proved that some respondents were aware of the particular consonants, although they fell back into Sasaknese phonological system when they lost their concentration.